A Discourse Analysis on Dialogues in Novels and its Implication to Improve Students’ Reading Comprehension - Arum Priadi (Universitas Negeri Padang, 2014)
This research aims at discovering the patterns of mistakes made by his students in interpreting novels’ dialogues that lead to misinterpretation. Those patterns then are modified by discourse analysis. During his experience teaching critical reading class, moreover, they were still weak to comprehend the dialogues; therefore, their comprehension went wrong. Consequently, they could not connect information among sentences which are related to each other. Accordingly, the ability to link among ideas in dialogues is badly needed for students to support their arguments in analyzing text. For that reason, the researcher offers the study of discourse analysis as one of the alternative solution.The researcher takes students of critical reading class as its research object while he uses his students’ works as his research source of the data. The students’ works contain misinterpretation through novels’ dialogues. Then, those works are documented as the data source to observe. As this study is qualitative, the researcher turns out to be the data instrument. The researcher himself determines how the data are accomplished to observe then to interpret. They were chosen based on research purpose; that is, modifying students’ misinterpretations using discourse analysis. It was carried out in order to make the analysis can be more meaningful since the researcher himself selected the data that are possible to support the research purpose; therefore, this research uses purposeful sampling.The data shows that the students do not use discourse context in their analysis such as reference, presupposition, implicature, and inference since dialogues in the novels consist of embedded aspects which is absolutely tied with context surrounding the sentences. To overcome those problems, therefore, the researcher provides discourse analysis involving the discourse contexts that will make analysis more accurate. Moreover, discourse analysis helps students to be more critical. Thus, their reading comprehension improves significantly because they analyze from overall views.